The Lord of the Flaws. The Autonomy of the Artist and the Function of Art - Schmücker, Reinold (The Nordic Journal of Aesthetics, 2010)
In aesthetics a misleading idea of autonomy prevails: art is autonomous because it does not serve any heteronomous purposes. This conviction is deeply rooted in the philosophy of art from Romanticism to Heidegger and Adorno. However, it is not convincing because art is functional in various ways. It can have a variety of very different purposes – including some that the artist does not approve. Against this background, the article focuses on a peculiarity of modern aesthetics which has not been noticed so far: the development of the modern concept of art has made the category of the mistake almost disappear. Works of art are taken to be something given which is not supposed to be examined for mistakes but to be explained and made understandable by the artistic decisions they are based on. By reflecting this peculiarity, the author develops an understanding of the autonomy of art as a normative artistic competence, which is compatible with the functionality of works of art and can help to clarify the social importance of art.